Pengaruh Storytelling dan Guided-Imagery terhadap Tingkat Perubahan Kecemasan Anak Usia Prasekolah yang Dilakukan Tindakan Invasif - Julita Rosalia Legi; Suhendar Sulaeman; Nyimas Heny Purwanti (Journal of Telenursing (JOTING), 2019)
This study aims to identify the effect of storytelling and guided imagery on changes in anxiety levels of preschool children who will be subjected to invasive action (infusion). The research design used was a quasi experiment. The results showed that the average level of anxiety of children who received storytelling intervention was 2.11 for the group of children who were accompanied by their parents and 2.50 for the group of children who were not accompanied by their parents. Meanwhile, the average level of anxiety of children with guided imagery intervention was 2.17 in the group of children accompanied by their parents and 2.33 in the group of children who were not accompanied by their parents. The results of statistical tests show that there is an effect of storytelling and guided imagery on reducing anxiety levels of preschool children who are subjected to invasive action (infusion). In conclusion, storytelling to preschool age groups accompanied by parents is more influential than to children who are not accompanied by their parents. Keywords: Guided-imagery, Preschool Anxiety, Storytelling